(untitled) - Tudor, Tasha (New York, 2001)
While awaiting the arrival of Easter, a child dreams of rabbits with shining eyes, little lambs, Easter ducklings, and other wonderful surprises.
Keywords: Animals; Easter; Fiction; Fiction